Surviving Cissy : my family affair of life in Hollywood - Garver, Kathy, 1945- (Taylor Trade Publishing, 2015)
"Kathy Garver, the heartthrob from the hit series Family Affair, was a journeywoman actress who appeared in such classic films as The Ten Commandments long before her television notoriety. This memoir is a recollection of a working actress's life, from the many films, television shows, and stage plays in which she performed, to her second career as a voice-over specialist"--